Comparison between Intracorporeal Pneumatic Lithotripsy and Extracorporeal Shock Wave Lithotripsy (ESWL) in terms of efficacy and Safety for Management of Proximal Ureteric Stones - Muhammad Amjad, Imran Hyder, Rana Ata Ur Rehman, Hammad Shafi, Muhammad Seerwan, Ali Shandar Durrani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare efficacy and safety of intracorporeal pneumatic lithotripsy versus extracorporeal shock wave lithotripsy (ESWL) in patients of upper ureteric stones having stone size from 10 to 15 mm. Study Design: Randomized control trial Setting: Study was done at department of Urology, Nishtar Hospital Multan. The duration of the study was from January 2021 to January 2022. Methodology: 140 patients were divided into two groups randomly. In group A ureterorenoscopy (URS) with Pneumatic Lithotripsy was used for proximal ureteric stones management. URS was performed under general anesthesia. In group B, ESWL was done for the management of proximal ureteric stones identified by ultrasound and fluoroscopy. SPSS version 23 was used for data analysis. Results: In this study In Intracorporeal Pneumatic Lithotripsy group the stone cleared in 90% patients and in ESWL group the stone cleared in 78.6% patients (p-value=0.595). In Intracorporeal Pneumatic Lithotripsy group the pain was present in 14.3% patients and in ESWL group the pain was present in 18.6% patients (p-value=0.494). In Intracorporeal Pneumatic Lithotripsy group the bleeding was noted in 25.7% patients and in ESWL group the bleeding was noted in 40.0% patients (p-value=0.072). Conclusion: This study concluded that intracorporeal pneumatic lithotripsy is a good alternate of ESWL for the management of upper ureteric stones (having size from 10 to 15mm). Keywords: Urolithiasis, Intracorporeal Pneumatic Lithotripsy, Extracorporeal Shock Wave Lithotripsy, Ureteric Stone